Mixed signals eaudiobook - Borison, B.K (Lovelight, 2022)
Layla Dupree has given up on love. She's waded through all of the fish in the sea, each one more disappointing than the last. Apparently owning the bakery at Inglewild's most romantic destination does not help one's love life—despite her best efforts. All she wants is a partner who gives her butterflies, not someone who ghosts her at dinner and leaves her with the check. Good thing Caleb Alvarez has the perfect solution. After saving Layla from another date gone bad, he has a simple proposition: one month of no-strings dating. He'll do his best to renew her faith in men, while she rates his dating game. It's a win-win situation. All the benefits of dating, without the added pressure of feelings and unmet expectations. But there's one ingredient they haven't considered: the chemistry between them is red hot, and the urge to take things to the next level is more tempting than Layla's double fudge mocha brownies. Will the heat between them boil over? Or will it be another case of mixed signals?